Influência do mercado do petróleo no Índice de Desenvolvimento Humano (IDH): comparação entre Brasil e Oriente Médio de 1996 a 2013 - Ferreira, Rafael Henrique Mainardes (2018)
This research aims to analyze the influence of the oil market on the Human Development Index (HDI) in Brazil and the Middle East from 1996 to 2013. The discussion of the literature in the present research consisted of a bibliometry, whose most influential factors of this thematic in global and regional scale, were subjects related to Health and Environment, Natural Gas and Biodiesel in national surveys; as well as the incidence of the issues of Governance and Petroleum Policy and Petrochemical and Petroleum Industry in international research. After a bibliometric verification, quantitative labor criteria were used through the United Nations Industrial Development Organization (UNIDO) database, version INDSTAT2 2013, ver. 4 - developed by the United Nations, in order to analyze the relationship between the variables that impact the oil and HDI market, comparing the countries that make up the Middle East and Brazil. As final conclusions of the study, it was verified that, of the three hypotheses drawn for the research - being H1, the oil market exerts greater influence on the HDI in the Middle East when compared to Brazil, making the region more dependent on the input; H2, the oil market has moderately influenced the Brazilian HDI between the period investigated; Finally, in H3 we investigated: the oil market has strongly influenced the HDI of the Middle East between the period investigated; it was possible to infer that only the second hypothesis was accepted, through statistical analysis. The other hypotheses were refuted, taking as elements of discussion the literature pertinent to the subject and covering new possibilities of discussions. It is necessary to deepen discussions on the axes of governability, diplomatic relations and relations between the elements that make up the quality of life of the subjects of each nation, with investigation of the influences or impacts on this market, at a global level.